Role of [Ca2+]i and F-actin on mesothelial barrier function - Kuwahara, Masayoshi (Frontiers in Physiology, 2014)
The mesothelial layer acts as a biological barrier between the organ and the enveloping serous cavity and may have functions of transport, equilibrium maintenance, and protection. However, the role of the mesothelial cells in regulation of pleural permeability remains essentially undefined. The present study was designed to clarify the effects of bradykinin, histamine, and thrombin on permeability in pleural mesothelial cells. Rat pleural mesothelial cells were cultured in vitro, and the permeability of mesothelial monolayers was evaluated by transmesothelial albumin diffusion and electrical resistance measurements. Furthermore, the temporal relationship between changes in the levels of [Ca2+]i and the mesothelial permeability was examined. Bradykinin (10 M), histamine (1 mM), and thrombin (10 U) caused albumin diffusion within 5 min. The electrical resistance of mesothelial monolayer began falling within 5 min of adding each agent. Time and concentration dependency of changes in electrical resistance were almost the same as that in albumin diffusion. Each agent also induced a biphasic elevation of [Ca2+]i in pleural mesothelial cells. The concentration-dependency of the [Ca2+]i responses were almost similar to that noted for each agent induced albumin diffusion and electrical resistance fall. The increase in permeability occurred with reorganization of F-actin cytoskeleton and increased actin polymerization. These results suggest that the Ca2+- dependency of increases induced by these agents in mesothelial permeability have been related to the regulatory role of Ca2+ in the F-actin cytoskeletal reorganization in pleural mesothelial cells.